Implementation Of Tourism Organization Guidelines Based On Sharia Principles Reviewed From Dsn-Mui Fatwa No.108/Dsn-Mui/X/2016 (Case Study Of The Madinah Syariah Hotel In Pamekasan) - Yuli Fransiska Dewi; Muhammad Ersya Faraby (JOURNAL OF SHARIA ECONOMICS, 2023)
This research discusses the implementation of guidelines for organizing sharia tourism based on DSN-MUI Fatwa NO.108/DSN-MUI/X/2016, where the sharia tourism that researchers are careful about is in the form of sharia accommodation. Therefore, researchers are interested in examining more deeply one of the sharia hotels in Pamekasan, namely the Madinah Syariah Hotel in Pamekasan. The research method used by researchers in this research uses descriptive qualitative methods with the research subjects being managers and employees of the Madinah Syariah Hotel in Pamekasan. The data used is primary data as well as secondary data, while data collection uses interviews, observation and documentation. The data analysis stage was carried out by means of data reduction, data display , and drawing conclusions. The research location is the Madinah Syariah Hotel in Pamekasan. The aim of this research is to determine the implementation of tourism administration guidelines based on sharia principles in terms of DSN-MUI Fatwa NO.108/DSN-MUI /X/2016 at the Madinah Syariah Hotel in Pamekasan